Effect of pre-harvest organic cytokinin application on the post-harvest physiology of pepper (Capsicum annuum l.) - Çavuşoǧlu, Şeyda; Sensoy, Suat; Karataş, Arzu; Tekin, Onur; İşlek, Fırat; Yilmaz, Nurettin; Kipçak, Selma; Ercıslı, Sezai; Skrovankova, S.; Adámková, Anna; Mlcek, Jiri (MDPI AG, 2021)
Peppers are cultivated in almost all provinces in Turkey, making up approximately 7% of the world’s production. In this study, the effects of pre-harvest cytokinin application on the postharvest physiology of pepper (Capsicum annuum L.) fruits (cv. Akra and Melek F1) grown in ecological conditions in Turkey (Van, eastern Turkey) were investigated. During the growing period, organic cytokinin(nytrozine) at two concentrations (50 and 100 ppm doses) was applied by spraying. Peppers were harvested in green maturity and then stored at 12 °C for 28 days. Changes in color, respiration rate, exogenous ethylene amount, antioxidative enzyme analysis (SOD, CAT and APX), lipid peroxidation, total phenolic content (TP) and antioxidant activity (AA) were determined just after the harvest and then at the 7th, 14th, 24th and 28th days. L* values for both varieties and the control sample had fluctuations during storage, and they slightly decreased after 28 days, except for the end value of cv. Melek F1 with a 50 ppm addition. In terms of respiration rate values, the difference between applications was found to be statistically significant, except for the 14th and 24th days of storage, for cv. Akra F1; and the 0th and 28th days for cv. Melek F1, respectively. It was observed that cytokinin can delay aging in peppers of both cultivars stored for 28 days. As a result, as the used cytokinin has an organic origin, is not synthetic and does not have a negative effect on human health, it can be used safely and without a significant loss of quality characteristics for peppers. These applications have positive effects on in-package gas composition, antioxidative enzymes, lipid peroxidation, total phenolics and total antioxidant activity. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.
Keywords: Antioxidative enzyme; Bioactive content; Cytokinin; Pepper; Respiration; Storage